PELAYANAN TICKETING DI PT. BINTAN TOUR AND TRAVEL MEDAN PROVINSI SUMATERA UTARA - Sari, Yuni Gloria; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of conducting this research is to know the quality of ticketing service in PT. Bintan Tour & Travel Medan. In this service quality consist of five (5) factors to be seen which factor is the most dominant in the process of quality ticketing service in PT. Bintan Tour & Travel Medan. This research uses descriptive quantitative methode to analyze the problems. The population of this research are consumers who came to buy tickets in PT. Bintan Tour & Travel Medan. The sampel of this research was 55 respondents, and its taking by Accidental Sampling tecnique based on convinience. Dimension of service quality, measuring the quality of service means evaluating the performance of a service with a set of predetermined standards, Tangible, Reliability, Responsiveness, Assurance, dan Empathy. Based on the research that has been conducted, respondents agree with five dimensions of service quality, consumers get results agree, consumers give a very good response and the dominant dimensions is Empathy. Keywords: Service, Tangible, Reliability, Responsiveness, Assurance, and Empathy